Hard loving cowboy - Pine, A. J.; Richardson, Sara (Romance fiction writer) (Pine, A. J. Crossroads Ranch novel., 2019)
Walker Everett spends his days at the Crossroads Ranch wrangling cattle-and steering clear of anything that would complicate his already too-complicated life. Until Violet Chastain, the ranch's newest employee, asks him to pretend to be her boyfriend for her parents' anniversary party. She's the most beautiful woman he's ever met and needs his help. How can he refuse? Violet isn't about to fall for a brooding bad-boy cowboy, no matter how sizzling their chemistry. But she also never expected Walker to go along with the charade. Before long, he's charming her parents at their weekly dinners and kissing her way more than necessary. Spending so much time together tests the limits of their "just friends" relationship, but what happens when their game of pretend becomes all too real?